The Management of the Principal in Enhancing Teachers’ Performance at MTS Darul Hikmah, Manggis Village, Ngancar Subdistrict, Kediri Regency - Suyanto S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the management of madrasah principals and teacher performance as well as to find out the management of madrasah principals in improving teacher performance and to identify the supporting and inhibiting factors for implementing madrasah principal management in improving teacher performance at MTs. Darul Hikmah Manggis Village, Ngancar District, Kediri Regency. This study uses a qualitative research approach to describe the problem of madrasah principal management in improving teacher performance. The data collection method consisted of field observations, in-depth interviews and documentation studies. Data were obtained from the head of madrasah, deputy head of madrasah and teachers of MTs. Darul Hikmah. The research results show that madrasah principal management can improve teacher performance through planning, organizing, implementing and supervising management functions. Teacher performance is assessed from improving teacher discipline, strengthening teacher motivation, teacher training programs and giving awards to teachers. Supporting factors include collaboration in task division, regular meetings, mastery of subject matter, and exemplary madrasah principals. Inhibiting factors include incomplete madrasah facilities, government regulations, some undisciplined teachers, uneven teacher skills, and lack of assertiveness in rule enforcement.